2017
DOI: 10.3389/fnagi.2017.00126
|View full text |Cite
|
Sign up to set email alerts
|

Current Experimental Studies of Gene Therapy in Parkinson's Disease

Abstract: Parkinson's disease (PD) was characterized by late-onset, progressive dopamine neuron loss and movement disorders. The progresses of PD affected the neural function and integrity. To date, most researches had largely addressed the dopamine replacement therapies, but the appearance of L-dopa-induced dyskinesia hampered the use of the drug. And the mechanism of PD is so complicated that it's hard to solve the problem by just add drugs. Researchers began to focus on the genetic underpinnings of Parkinson's diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 109 publications
0
13
0
Order By: Relevance
“…Most of the drugs utilized for the treatment of PD essentially works by enhancing dopaminergic neurotransmission, among which Levodopa (L-Dopa) is the most effective drug to treat motor symptoms in early and advanced stages of PD ( 8 , 12 , 13 ). Except for L-Dopa (precursor of Dopamine), current therapies can be divided into “dopaminergic” and “non-dopaminergic” drugs ( 14 ). The first class of drugs includes dopamine receptor agonists (e.g., apomorphine), catechol-O-methyltransferase (COMT, e.g.…”
Section: Overview On Parkinson's Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Most of the drugs utilized for the treatment of PD essentially works by enhancing dopaminergic neurotransmission, among which Levodopa (L-Dopa) is the most effective drug to treat motor symptoms in early and advanced stages of PD ( 8 , 12 , 13 ). Except for L-Dopa (precursor of Dopamine), current therapies can be divided into “dopaminergic” and “non-dopaminergic” drugs ( 14 ). The first class of drugs includes dopamine receptor agonists (e.g., apomorphine), catechol-O-methyltransferase (COMT, e.g.…”
Section: Overview On Parkinson's Diseasementioning
confidence: 99%
“…Current non-dopaminergic drugs mainly work as antagonists of NMDA (N-methyl-D-aspartate) receptor (such as Amantadine) providing mild benefits and reducing LID. Other non-dopaminergic drugs are still under preclinical and clinical trials (e.g., metabotropic glutamate receptor antagonists) ( 14 ). Moreover, small molecule epigenetic modulators targeting DNMTs (DNA methyltransferase), HDACs (Histone deacetylase) and HATs (Histone acetyltransferase) are also undergoing preclinical and clinical trials as novel therapeutic tools for PD ( 15 ).…”
Section: Overview On Parkinson's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Gene therapy (Collins and Thrasher, 2015 ) for example has been attempted long before optogenetics was even conceived. Direct insertion of functional proteins (Lin et al, 2017 ) or optic control of these proteins (Brechun et al, 2016 ) have also been suggested. The observation of Parkinson symptoms improvement after a localized brain lesion (Dubois et al, 1986 ) inspired the use of stereotactic brain surgery in patients.…”
Section: A Multidisciplinary Contextmentioning
confidence: 99%